(untitled) (Biological Sciences - PJSIR, 1999)
The granules of D. dumetorum starch are very fine (about 2- 5 microns). Table 1shows the percentage of starch extracted from the white and yellowcultivars. It isevident that the starch content of D. dumetorum is far lower than those of most substances commonly used as starch food materials.